Pemberdayaan Masyarakat Melalui Pemanfaatan Ekstrak Pandan dalam Pembuatan Sabun Ramah Lingkungan di Kelurahan Sadeng Kecamatan Gunungpati Kota Semarang - Siti Rodhotul Jannah; Dina Ma’rifatul Khoiriyah; Reza Khilmah Yunika; Eka Vasia Anggis (Jurnal Kemitraan Masyarakat, 2024)
The utilization of natural materials in household products is increasingly in demand along with the increasing awareness of the importance of maintaining environmental sustainability.One innovative way to utilize natural materials is by utilizing pandanus leaves into natural dyes. Pandanus extract was chosen because of its active compounds that have antibacterial properties and a refreshing aroma.This activity was carried out with the women of the Forum Kesehatan Keluarga (FKK) in Jogoprono RW VI Sadeng Village, Gunungpati District, Semarang City. The purpose of this activity is to increase community awareness and skills in using environmentally friendly soaps that are not only beneficial for health but also contribute positively to the environment.The methodology used in this paper uses a qualitative method with an experimental approach.The results of the activity show that the utilization of pandanus extract in liquid soap not only provides an alternative cleaning product that is safer for the environment but also empowers the local community through active involvement in the production process. In addition, this activity is expected to serve as a model for similar initiatives in creating eco-friendly products that empower communities and support environmental conservation.